1997
DOI: 10.1046/j.1365-2303.1997.45582455.x
|View full text |Cite
|
Sign up to set email alerts
|

Audit of 6 years' experience of breast fine needle aspiration (FNA) cytology using the cytospin method; improvement through multidisciplinary clinical audit

Abstract: A breast FNA cytology service for palpable breast lumps was commenced in 1989 using the cytospin method. Over the following 6 years 2314 aspirates were received. The results were audited in detail in 1990, 1991/1992 and 1994. Multidisciplinary clinical audit meetings followed each audit cycle. Practice change was agreed after each audit. Each audit cycle was followed by demonstrable improvement in the complete sensitivity of the technique, being respectively 79%, 88% and 96%. The cytospin method is a viable al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The experience and skill of the aspirator is probably the most important factor in reducing inadequate sample rates. 3,4 There were, however, insufficient data in our series to substratify the results between different grades of doctors and individuals. We calculated an 8.5% incidence of breast cancer among inadequate breast specimens.…”
Section: Discussionmentioning
confidence: 88%
“…The experience and skill of the aspirator is probably the most important factor in reducing inadequate sample rates. 3,4 There were, however, insufficient data in our series to substratify the results between different grades of doctors and individuals. We calculated an 8.5% incidence of breast cancer among inadequate breast specimens.…”
Section: Discussionmentioning
confidence: 88%
“…A number of recent studies have shown that the Cytospin method is an acceptable alternative to direct smears for FNA of breast 9–12 ; complete sensitivity (the proportion of malignant lesions correctly diagnosed or diagnosed as suspicious FNA) in two studies 9 , 10 was approximately 96%, excluding inadequates, comparing favourably with figures from studies using direct smears 13–15 . The inadequate rate was 5–15%, again comparing well with most direct smear reports 14 ; in general a lower inadequate rate is achievable when one aspirator, often a cytopathologist, takes all the aspirates 16 .…”
Section: Is the Cytospin Methods For Fna Of The Breast An Acceptable Amentioning
confidence: 99%
“…The inadequate rate was 5-15%, again comparing well with most direct smear reports 14 ; in general a lower inadequate rate is achievable when one aspirator, often a cytopathologist, takes all the aspirates 16 . As with all FNAs, by whatever method, the positive predictive value for malignancy (the fraction of malignant FNAs that was confirmed malignant on histology or was clinically an advanced fungating tumour) is almost 100% [9][10][11][12][13][14][15][16] .…”
Section: Is the Cytospin Methods For Fna Of The Breast An Acceptable Amentioning
confidence: 99%
“…FNA has a well‐established role in the preoperative diagnosis of breast lesions. In the literature, reports of FNA sensitivity and specificity for the diagnosis of breast malignancy by the cytospin technique (CyS) range from 79 to 96% and 80 to 97%, respectively 22, 23. As these figures compare favorably with those reported for DS, CyS has been accepted as a viable and accurate alternative to DS for breast FNAs 10, 22–25.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, reports of FNA sensitivity and specificity for the diagnosis of breast malignancy by the cytospin technique (CyS) range from 79 to 96% and 80 to 97%, respectively 22, 23. As these figures compare favorably with those reported for DS, CyS has been accepted as a viable and accurate alternative to DS for breast FNAs 10, 22–25. In contrast, studies of the ThinPrep® (TP) method show a sensitivity of 86–100% and specificity of 74–98% for the diagnosis of breast malignancy by FNA 8, 17, 26…”
Section: Discussionmentioning
confidence: 99%